Competitiveness of Indonesian Clove Exports in the International Market - Simarmata, Gerry Andrianto; Nurfadilla, Suryani; Ekowati, Titik (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 2 (2024): Vol 18 No 2 (2024)DO - 10.24843/SOCA.2024.v18.i02.p02, 2024)
Clove production in Indonesia is not only aimed at meeting domestic needs but also targeted to fulfill export demands in the international market. This study aimed to analyze the competitiveness of Indonesian clove exports and examine the factors influencing the volume of Indonesian clove exports to ten main destination countries. The research method utilized was Secondary Data Analysis. The data employed in this study consist of secondary data in the form of time series and cross-sectional data from the top ten destination countries for Indonesian clove exports during the period 2001 – 2022. The data analysis techniques included Revealed Comparative Advantages analysis and panel data regression (gravity model) using the Random Effect Model with Cross-Section Seemingly Unrelated Regression weighting. The research findings indicate that, in general, Indonesian clove commodities in the top ten destination countries exhibit strong competitiveness, as evidenced by the average Revealed Comparative Advantage (RCA) of Indonesian cloves in these countries being greater than one (>1). Additionally, the panel data regression results demonstrate that the real Gross Domestic Product per capita of Indonesia, the real Gross Domestic Product per capita of the destination countries, the population of the destination countries, and the real exchange rate have a positive and significant impact on the volume of Indonesian clove exports. Conversely, the economic distance variable has a negative and significant impact on the volume of Indonesian clove exports.